2022
DOI: 10.1136/lupus-2022-000726
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of the third and fourth BNT162b2 mRNA COVID-19 boosters and factors associated with immune response in patients with SLE and rheumatoid arthritis

Abstract: ObjectivesTo evaluate the safety and immunogenicity of third and fourth BNT162b2 boosters in patients with SLE and rheumatoid arthritis (RA).MethodsPatients with SLE and RA aged 18–65 years who completed a series of inactivated, adenoviral vector, or heterogenous adenoviral vector/mRNA vaccines for at least 28 days were enrolled. Immunogenicity assessment was done before and day 15 after each booster vaccination. The third BNT162b2 booster was administered on day 1. Patients with suboptimal humoral response to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
4
20
0
Order By: Relevance
“…Up to date, only one study evaluated both humoral and cellular responses after booster vaccination in AIIRD patients. Assawasaksakul et al assessed patients with systemic lupus erythematosus and RA and showed an increase in both humoral and cellular responses after the booster dose (33). The authors however did not compare it with a control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to date, only one study evaluated both humoral and cellular responses after booster vaccination in AIIRD patients. Assawasaksakul et al assessed patients with systemic lupus erythematosus and RA and showed an increase in both humoral and cellular responses after the booster dose (33). The authors however did not compare it with a control group.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, despite the commencement of widespread COVID-19 vaccination with booster doses in many countries around the world, data on the effectiveness of COVID-19 vaccine booster doses in patients with AIIRD is scarce (27,28). There are only a few studies describing the immunogenicity of a booster dose in AIIRD patients (29)(30)(31)(32)(33), but no study evaluating individual immunomodulatory drugs' effect on cellular response to booster dose in AIIRD patients. The aim of our study was therefore to assess the immunogenicity of a booster dose of COVID-19 vaccination on humoral and cellular levels in inflammatory arthritis (IA) cohort treated with immunomodulatory drugs.…”
Section: Introductionmentioning
confidence: 99%
“…However, booster vaccinations are given worldwide, and since patients with RMDs receive immunosuppressive drugs on a continuous basis, analysis of the effect of booster vaccinations is necessary in future vaccine medicine. [28–30]…”
Section: Discussionmentioning
confidence: 99%
“…However, booster vaccinations are given worldwide, and since patients with RMDs receive immunosuppressive drugs on a continuous basis, analysis of the effect of booster vaccinations is necessary in future vaccine medicine. [28][29][30] The American College of Rheumatology has provided guidance about the use and timing of COVID-19 vaccination concerning immunomodulatory therapy in patients with RMDs, but supportive evidence is limited. [1] The decision to suspend immunosuppressant therapy concerning COVID-19 vaccination in such patients should be based on disease activity and the effect of immunosuppressive treatment on the immunogenicity of the COVID-19 vaccine.…”
Section: Sugihara Et Al • Medicine (2022) Medicinementioning
confidence: 99%
“…People on treatment for autoimmune diseases tend to respond poorly to vaccination and have a greater need for vaccine boosters. However, in this population, the 4 th dose of mRNA vaccine did not improve protection against Omicron and further, it caused flare-ups of autoimmune diseases in some patients [ 13 ]. For elderly people, low-quality immune response to vaccination seem to be caused by a T cell repertoire-intrinsic defect that may not be rescued by repeated vaccination [ 14 ].…”
mentioning
confidence: 99%